The Ankle-Hindfoot Kinematics of Current Generation Total Ankle Replacement: A Cadaveric Gait Simulation. Issue 4 (16th October 2019) - Harnroongroj, Thos; Sturnick, Daniel; Ellis, Scott J.; Demetracopoulos, Constantine; Deland, Jonathan
Category: Ankle Arthritis Introduction/Purpose: Total ankle replacement (TAR) has developed as a standard treatment option for end-stage ankle arthritis with the primary benefit of pain relief and ankle-hindfoot motion preservation. The current generation of TARs features limited bone resection and improved initial fixation of components to restore physiologic constraint and the anatomic articulation of the ankle. However, the ankle-hindfoot kinematics of current TAR designs compared to the baseline native ankle have not yet been extensively studied. Cadaveric gait simulation is a valuable tool for investigating direct effects of surgical procedures on foot and ankle biomechanics. The objective of this study was to assess whether this current generation TAR system could provide normal ankle-hindfoot kinematics as the baseline native ankle using cadaveric gait simulation. Methods: Eleven mid-tibia cadaveric specimens were secured to a static mounting fixture with a six-degree of freedom robotic platform to simulate gait in native-intact and TAR conditions. A force plate was moved relative to the stationary specimen through an inverse tibial kinematic path calculated from in vivo data while extrinsic tendons were actuated using physiologic loads (Figure 1A). Ankle-hindfoot kinematics were measured from reflective markers attached to bones via surgical pins. TAR was performed using a current generation, fixed-bearing system by a fellowship-trained foot-ankle surgeon using the manufacturer described protocol (PROPHECY Patient-specific instrumentation, Infinity, Wright Medical Technology). Ankle-hindfoot joint kinematics were measured using the same tibial kinematic inputs and muscle forces as the intact condition. Non-parametric, bias-corrected bootstrapping was used to calculate 95% confidence intervals to compare motion between intact and total ankle replacement. Results: Analyses demonstrated no significant difference in average ankle-hindfoot joint kinematics between the intact and TAR conditions (Figure 1B). The result was consistent for the ankle, subtalar, and talonavicular joints, in each plane of motion. Conclusion: These findings demonstrate that the current generation of fixed-bearing TAR can recreate normal ankle-hindfoot kinematics patterns seen in normal ankles. Restoring ankle kinematics can be a significant factor in slowing down the progression of adjacent joint arthritis in the foot. However, it is still inconclusive whether ankle-hindfoot kinematics can be restored in patients with long standing ankle arthritis, and this should be addressed in future studies.